Design challenges and guidelines for free-space optical communication links using orbital-angular-momentum multiplexing of multiple beams. (14th June 2016) - Willner, Alan E; Xie, Guodong; Li, Long; Ren, Yongxiong; Yan, Yan; Ahmed, Nisar; Zhao, Zhe; Wang, Zhe; Liu, Cong; Willner, Asher J; Ashrafi, Nima; Ashrafi, Solyman; et al.
Abstract: In this paper, recent studies on the potential challenges for an orbital angular momentum (OAM) multiplexing system were reviewed. The design guideline for a practical OAM multiplexing system were investigated in term of (i) the power loss due to the beam divergence and limited-size receiver, and (ii) the channel crosstalk due to the misalignment between the transmitter and receiver.